IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) DI KABUPATEN KUTAI TIMUR - Rusmadi dan Achmad Zaini (Jurnal Borneo Administrator, 2009)
Kutai Timur was one of new established district in East Kalimantan that know as mining area and mostly of its local nature income from this business especially charcoal and agriculture. KPC, Rio Tinto, BP are examples of the largest company which has been investing in this area instead of many others on the same business with small size. As one of “rich” area, Kutai Timur seems like a bowl of sugar surrounded by ants who are ready to bring the sugar out. This was a big challenge not only for local government but also civil society to keep and usage their own resources to bring community and the area to become a model of on how the usage of natural resource could is governed and planed in participatory and transparent manner in order to bring welfare rather than conflict. This project was aimed to support initiative from civil society in reforming business through promoting participatory planning and corporate social responsibility (CSR) by multi stakeholder approach and initiatives in Kutai Timur. The activity of empowerment was did by formal and informal approach, workshop, focus group discuss (FGD) etc.  The model of CSR implementation in Kutai Timur was built  by the guidance of CSR implementation and “Multistakeholder-CSR Forum” with  participatory and  transparent principle.